Safe packaging for health food products - Mohd, M.A. (2012)
Packaging industries should be considering technology that creates a balance between food protections with other issues, including material costs, safety, social and environmental consciousness, and strict regulations on pollutants and disposal of municipal solid waste. The current issues in food packaging seem to focus mainly on general matters, while they are numerous safety, health and environmental impact issues that were not highlighted due to economics reasons. The health impact of packaging materials and chemical are has become more significant as new findings have shown that these chemicals may affect the reproductive system of babies and children and so adults. Some of these chemicals also may cause obesity and exert estrogenic affect s on women. Some of these materials release endocrine disrupting chemicals (EDC) into food and may exert several endocrine disruption effects and this may cause various adverse health effects. Some example of this materials are phtalates, bisphenol A and polybrominated compounds used in packaging materials. Endocrine disrupting chemicals are exogenous chemicals introduced into biological systems that may cause a derailment of the endocrine system causing the organism to have various hormone related health problems. The EDC exerts their effects in minute quantities and they act by receptor-mediated mechanism.